The Impact Online Customer Reviews, Discount, User Interface On Purchase Decision - Hana Diana Maria; Firdan Gusmara Kusumah; Adie Pamungkas; Elvira Natasya Maulida (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
The evolving industry has brought major changes to consumer behavior, where people now rely more on technology to fulfill their daily needs. Society is heavily influenced by technological advancements that drive a shift from traditional purchasing behavior to digitalization. Recommendations from friends, family, advertisements, and digital purchases are the main factors that influence purchasing decisions. In addition, online customer reviews and discounts are becoming important elements that influence consumer choices, allowing them to compare various products easily. The purpose of this research is to explore the extent to which online customer reviews, promotional discounts, and user interface features affect consumers' purchasing decisions on the Shopee platform within the context of Tasikmalaya City. This research applies quantitative and descriptive methods, through a causal associative approach. Sampling applied a simple random sampling technique where the total sample size was 390 respondents from a total population of 14,544 people. The data was processed and analyzed using the SPSS 2.0 software application. The results showed a significant influence of online customer reviews, discounts, and user interfaces on purchase decisions on the Shopee platform service application, both individually and simultaneously